1981
DOI: 10.1055/s-2007-971683
|View full text |Cite
|
Sign up to set email alerts
|

Die Flavonoide in den Blüten von Primula officinalis

Abstract: From methanolic extracts of fresh flowers of Primula officinalis 19 flavonoids were isolated or detected: quercetin, luteolin, kaempferol, isorhamnetin, apigenin; quercetin 3-O-glucoside, -rutinoside, -robinobioside, -gentiobioside, -(glucosyl-(1-->2) -glucosyl-(1-->6))-glucoside, -(rhamnosyl)-robinobioside; isorhamnetin 3-O-glucoside, -rutinoside, -robinobioside, -(rhamnosyl) -robinobioside; kaempferol 3-O-rutinoside, -robinobioside; limocitrin 3-O-glucoside; 3', 4'-dihydroxyflavonglucoside. Other compounds i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 3 publications
1
20
0
Order By: Relevance
“…(a synonym for P. veris L.). Strong variation in the compound concentration may also account for the absence of the flavonoids gossypetin, luteolin and apigenin in our samples, which have been reported for P. veris before [20]. …”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…(a synonym for P. veris L.). Strong variation in the compound concentration may also account for the absence of the flavonoids gossypetin, luteolin and apigenin in our samples, which have been reported for P. veris before [20]. …”
Section: Discussionsupporting
confidence: 62%
“…The occurrence of these two flavonoid glycosides was confirmed in the present work, and both were found in petals as well as leaves. Further quercetin derivatives have already been identified in previous studies of P. veris and P. elatior and were used for analytical differentiation between these two medicinal plants [20]. Quercetin-3-gentiobioside, quercetin-3- O -gentiotrioside, kaempferol-3- O -rutinoside and kaempferol-3- O -robinobioside were isolated from petals of the wild type P. veris [7] and were also detected in flowers and leaves of the current study.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The 15 known compounds were isolated and identified as quercetin (4), kaempferol (5), quercetin 3-O-methyl ether (6), 2,3-dihydrokaempferol (7) (Lee et al, 2003), isorhamnetin 3-O-glucoside (8) (Karl et al, 1981), 2,3-dihydroquercetin (9) (Nonaka et al, 1987), coumaric acid (10), kaempferol 7-O-glucoside (11) (Lee et al, 1998), ferulic acid (12), isorhamnetin 3-O-neohesperidoside (13) (Norbaek and Kondo, 1999) (14) (Aquino et al, 1987), isorhamnetin 3-O-(2,6-dirhamnosyl)glucoside (15) (Liu and Lu, 1998), zataroside-A (16) (Ali et al, 1999), n-butyl-b-D-fructopyranoside (17) (Xu et al, 2005), 4-O-glucosyl-mapic acid (18) (Materska and Perucka, 2005), the structure of which were determined by spectroscopic analyses.…”
Section: Resultsmentioning
confidence: 99%
“…It is a well-known medicinal plant, which provides rhizome and roots (Primulae radix) with an expectorant activity associated mainly with the triterpene saponins (Schö pke, 1994). The flowers of P. veris, of similar medicinal use (Primulae flos) (Schö pke, 1994), were found to contain a number of flavonol glycosides (Karl et al, 1981;Hegnauer, 1990) and several methoxyflavones (Huck et al, 1999(Huck et al, , 2000Stecher et al, 2003), the latter representing a group of lipophilic flavonoids found earlier in the leaf exudates of some Primula species (Hegnauer, 1969(Hegnauer, , 1990Wollenweber et al, 1988Wollenweber et al, , 1990Wollenweber and Mann, 1986). A few flavonoids were also detected in the leaves of P. veris (Harborne, 1968;Hegnauer, 1990).…”
Section: Introductionmentioning
confidence: 99%